Three Major Problems Threatening Multi-National Pharmaceutical Companies Doing Business in China - Chow, Daniel C.K. (Science and Technology Law Review, 2018)
Multi-National Companies (MNCs) in the pharmaceutical industry today face formidable challenges in China, the world’s second-largest pharmaceutical market after the United States. Not only is China the world’s largest source of counterfeit and substandard drugs, Chinese authorities have also recently targeted MNCs as part of a crackdown on bribery and competition law violations. In addition, China has a number of technology transfer laws that seem designed to force MNCs to provide uncompensated access to their proprietary technology protected by patents and trade secrets. All of these problems can be traced to China’s rising nationalism and protectionism in its dealings with foreign companies and nations in international business and trade. These are daunting problems, but while MNCs focus their efforts on short-term technical solutions, only a long-term approach focusing on legal and political reform can provide a lasting solution.